Institutional ranking in a differentiated higher education in South Africa - Ntshoe, Isaac; Selesho, JM (South African Journal of Higher Education, 2016)
Ranking institutions on a league table style is used either explicitly or implicitly by agencies to determine the excellence, performance and reputation of higher education institutions (HEIs). However, there is a growing concern that this tool tends to encourage the drift of missions, foci, purposes and specialisations of knowledge and skills produced by different HEIs globally. This article takes issue with the widely accepted practice of ranking institutions on a league table style. Drawing examples from South Africa, the article begins by describing the inherent drawbacks of league table approaches and proposes alternative forms of determining the performance of HEIs. This is followed by a discussion on South Africa, highlighting the challenges of league table styles to rank HEIs in systems where institutions are differentiated in terms of their purpose and mission, and how these might subtly encourage mission drift. The third section is devoted to the discussion and conclusion.
Published Article
Keywords: institutional ranking; differentiated foci; mandates; U-Map; U-Multirank